Vitamin D Therapy Attenuates Symptoms of Painful Diabetic Peripheral Neuropathy (PDPN) in T2DM patients - Moeen Akhtar Malik, Junaid Mustafa, Nayyara Tahir, Mazhar Hussain, Habib Ur Rehman, Muhammad Umar Waheed, Hafiz Naveed Anjum (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the outcome of oral vitamin D therapy on symptoms of PDP Nin T2DM patients Methods: This randomized double blind placebo controlled trial comprised 120 T2DMpatients with vitamin D deficiency and symptoms of PDPN on the basis of neuropathy symptoms score (NSS) and neuropathy disability score (NDS). Patients were randomly divided in to two groups. Patients in group A were given capsule vitamin D2, 00000IU/month over while patients in group B were given capsule placebo for a period of 03 months duration. The study outcomes of PDPN were assessed by NSS and NDS as primary endpoint while glycemic control and vitamin D level were secondary end point of study from baseline. Results: After 12 weeks therapy of vitamin D, significant improvements were recorded in primary end points NSS score (from 5.9±2.0 to 4.7±1.5 ) vs placebo (6.5 ±2.0 to 6.4 ±3.2) with p-value (0.002) and NDS score (from 7.8±2.0 to 6.5± 2.5) vs placebo (7.7±1.8 to 7.9±2.5) with p-value (0.001). Similarly secondary endpoints were also improved significantly from baseline to end point after 12 weeks of vitamin D therapy vitamin D value ( from 25.8±14 to 44.5±12.5) vs placebo group ( from 28.5±14.5 to30.0±15.5) with p-value (0.002), HbA1c from 9.0±2.8 to 7.8±3.5) vs Placebo ( from 9.8±2.0 to 9.5±2.2) with p-value 0.001 (table 2). Conclusion: Vitamin D therapy attenuates symptoms of PDPN in T2DM patients